Kosterlitz-Thouless-type caging-uncaging transition in a quasi-one-dimensional hard disk system - A. Huerta; T. Bryk; V. M. Pergamenshchik; A. Trokhymchuk (Physical Review Research, 2020)
The simplicity of a quasi-one-dimensional system of hard disks enables us to get a much deeper and more quantitative insight into the solid-to-fluid transformation and identify it as caging-uncaging transition. Both computer simulation data and theoretical results show that density decrease induces progressively larger number of uncaged disk pairs which exchange their transverse positions through windows in the initial crystalline zigzag array. At low densities windows dominate and disks are moving independently (pairs “dissociate”). Along with the simulation data on the transversal excitation modes and pair correlation function this shows that the solid-to-liquid transformation is a continuous Kosterlitz-Thouless-type transition.